2014
DOI: 10.1007/s12149-014-0873-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 123I-MIBG myocardial scintigraphy, brain perfusion SPECT, and voxel-based MRI morphometry for distinguishing between dementia with Lewy bodies and Alzheimer’s disease

Abstract: (123)I-MIBG myocardial scintigraphy was superior to brain perfusion SPECT and brain MRI using an advanced statistical technique to differentiate DLB and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…In addition, one case clinically diagnosed with PSP, for which there was a decrease in the cardiac MIBG uptake in the early as well as in the delayed phases, was diagnosed with DLB after post-mortem pathology. It has been previously reported that 123 I-MIBG cardiac scintigraphy has a high sensitivity and specificity for the differentiation between LBD and other related disorders 6 7. Furthermore, our results also confirmed that this technique is a useful tool for the clinical differentiation of LBD from other parkinsonism.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, one case clinically diagnosed with PSP, for which there was a decrease in the cardiac MIBG uptake in the early as well as in the delayed phases, was diagnosed with DLB after post-mortem pathology. It has been previously reported that 123 I-MIBG cardiac scintigraphy has a high sensitivity and specificity for the differentiation between LBD and other related disorders 6 7. Furthermore, our results also confirmed that this technique is a useful tool for the clinical differentiation of LBD from other parkinsonism.…”
Section: Discussionsupporting
confidence: 87%
“…This technique is useful during clinical diagnosis because it has a high sensitivity and specificity to differentiate LBD from other related neurological disorders such as progressive supranuclear palsy (PSP), multiple system atrophy (MSA), corticobasal degeneration or AD 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ROC analysis based on the Z-score indicative of hypoperfusion is necessary to examine the discrimination power of these abnormal findings [26]. For the quantitative assessment of Z-scores in abnormal regions, the vbSEE program is a useful method by classifying stereotactic brain coordinates according to the anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 123 I]MIBG is a promising biomarker with the ability of excluding AD and predicting conversion of possible to probable DLB [8789]. A large multicenter study including 133 patients, diagnosed according to the consensus criteria, highlighted similar sensitivity and specificity to [ 123 I]FP-CIT-SPECT [90, 91].…”
Section: Molecular Imagingmentioning
confidence: 99%